2002
DOI: 10.1029/2001gl014498
|View full text |Cite
|
Sign up to set email alerts
|

A sudden bottom‐water formation during the severe winter 2000–2001: The case of the East/Japan Sea

Abstract: We observed a sudden initiation of bottom‐water formation in the East/Japan Sea associated with a severely cold winter in 2000–2001. An increase in dissolved oxygen concentration as well as decreases in temperature and nutrient concentrations for the bottom waters provides unequivocal evidence that cold, oxygen‐rich and nutrient‐poor surface waters were injected directly to the bottom. Since the conveyor‐belt in the East Sea has been undergoing dramatic change with a complete halt to bottom‐water formation sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 15 publications
7
78
0
1
Order By: Relevance
“…20(a)) could be related to the following event: a sudden formation of bottom water, probably during the severely cold winter of 2000-2001. This event was identified from water column anomalies of chemical tracers (dissolved oxygen, nutrients, and chlorofluorocarbons) just above the seafloor in the coastal zone off Vladivostok in the summer of 2001 (Kim et al, 2002;Senjyu et al, 2002;Talley et al, 2003;Tsunogai et al, 2003). By using moored current meters, Senjyu et al (2002) observed strong bottom currents up to 8 cm s −1 from mid-February 2001, suggesting a spin-up of the thermohaline circulation in the Japan Sea.…”
Section: Temporal Change Of the Japan Sea Bottom Watermentioning
confidence: 99%
“…20(a)) could be related to the following event: a sudden formation of bottom water, probably during the severely cold winter of 2000-2001. This event was identified from water column anomalies of chemical tracers (dissolved oxygen, nutrients, and chlorofluorocarbons) just above the seafloor in the coastal zone off Vladivostok in the summer of 2001 (Kim et al, 2002;Senjyu et al, 2002;Talley et al, 2003;Tsunogai et al, 2003). By using moored current meters, Senjyu et al (2002) observed strong bottom currents up to 8 cm s −1 from mid-February 2001, suggesting a spin-up of the thermohaline circulation in the Japan Sea.…”
Section: Temporal Change Of the Japan Sea Bottom Watermentioning
confidence: 99%
“…울릉분지 해역의 심층수는 울릉 분지 간 평원(Ulleung Interplain Gap: UIG)을 통해서 외 부와 순환을 하고 있는데, 심층수의 교환이 가능한 유일한 경로이다. 일본분지에서 심층수가 형성되고 (Seung and Yoon 1995;Kim et al 2002), UIG를 통하여 일본분지에 서 울릉분지로 동해심층수가 흘러 들어간다. 울릉분지에 서 해수의 수직적 순환에는 약 100년이 걸리고, 심층수가 완전히 바뀌는 데는 약 1,000년이 걸리는 것으로 보고되 고 있다 (Tsunogai et al 1993;Chen et al 1995).…”
unclassified
“…The East/Japan Sea (EJS) in the Northwest Pacific Ocean is a typical semi-closed marginal sea with a surface area of 1.01 Â 10 6 km 2 and a maximum depth of >3700 m. Because it has its own deep convection system (thermohaline conveyor belt), which is independent of the Pacific Ocean, the EJS has been regarded as a miniature of the global ocean in terms of deep water formation (Kim et al, , 2002Gamo et al, 2001). The EJS water is separated into colder water (North Korea Cold Current) to the north and warmer and more saline water to the south (Tsushima Warm Current).…”
Section: Study Areamentioning
confidence: 99%